Iowa Birdline update, February 18, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of the Iowa Birdline update for February 18, 1991. Highlights include large numbers of diving ducks and gulls along the Mississippi River as far north as Le Claire. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed